2021
DOI: 10.3389/fonc.2020.584024
|View full text |Cite
|
Sign up to set email alerts
|

The Cancer/Testis Antigen Gene VCX2 Is Rarely Expressed in Malignancies but Can Be Epigenetically Activated Using DNA Methyltransferase and Histone Deacetylase Inhibitors

Abstract: Identification of novel tumor-specific targets is important for the future development of immunotherapeutic strategies using genetically engineered T cells or vaccines. In this study, we characterized the expression of VCX2, a member of the VCX/Y cancer/testis antigen family, in a large panel of normal tissues and tumors from multiple cancer types using immunohistochemical staining and RNA expression data. In normal tissues, VCX2 was detected in the germ cells of the testis at all stages of maturation but not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…The expressions of the SSX1 and SSX2 genes were found in the advanced grades of CC tissue samples, according to the clinical data of the study participants (grades II and III). Consistent with previous reports on SSX family expression in a range of human cancers (9,17,18), SSX gene expression has been correlated with more advanced stages of disease [23][24][25]. Previous studies have identified the same findings for SSX genes in patients with CC [17].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The expressions of the SSX1 and SSX2 genes were found in the advanced grades of CC tissue samples, according to the clinical data of the study participants (grades II and III). Consistent with previous reports on SSX family expression in a range of human cancers (9,17,18), SSX gene expression has been correlated with more advanced stages of disease [23][24][25]. Previous studies have identified the same findings for SSX genes in patients with CC [17].…”
Section: Discussionsupporting
confidence: 88%
“…DNA methylation and histone acetylation are epigenetic processes that have been shown to influence the expressions of various CT genes [ 7 , 9 , 11 , 18 ]. With regard to DNA methylation, DNA methyltransferase enzymes (DNMTs) control the expressions of diverse CT genes by adding large amounts of a methyl group (CH₃) to their promoter regions, silencing them.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, hypomethylating agents upregulate the antigen presentation machinery and cancer testis antigens in solid and hematological cancer cells (Siebenkäs et al., 2017; Srivastava et al., 2016). Importantly, cancer testis antigens are highly immunogenic tumor‐specific antigens that are expressed aberrantly in several cancer types and are the focus of new immunotherapy targets (Jakobsen & Gjerstorff, 2020; Jakobsen et al., 2021).…”
Section: Improving Murine Models To Better Represent Human Cancers Fo...mentioning
confidence: 99%
“…The mechanisms that control the unusual MAGEAs are still under exploration. MAGEAs are infrequently express sues; however, epigenetic changes including DNA hypermethylation o tides in promoters and posttranslational modifications of the histone pro scription factors from binding, and thus represses the expression of MA Further studies have shown that DNA methyltransferases (DNMTs) inh aza-2-deoxycytidine, result in the increased expression of MAGEA1 in s cells [35]. This effect can be additionally reinforced using histone deac [35,36].…”
Section: Introductionmentioning
confidence: 99%